2012
DOI: 10.1037/a0026553
|View full text |Cite
|
Sign up to set email alerts
|

Navigation assistance: A trade-off between wayfinding support and configural learning support.

Abstract: Current GPS-based mobile navigation assistance systems support wayfinding, but they do not support learning about the spatial configuration of an environment. The present study examined effects of visual presentation modes for navigation assistance on wayfinding accuracy, route learning, and configural learning. Participants (high-school students) visited a university campus for the first time and took a predefined assisted tour. In Experiment 1 (n = 84, 42 females), a presentation mode showing wayfinding info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 67 publications
5
69
0
Order By: Relevance
“…Nowadays, mobile navigation systems take over guidance in real environments. This has detrimental effects on spatial learning: Münzer et al compared computer-assisted navigation to traditional map-based navigation and found differences in incidental knowledge acquisition (Münzer, Zimmer, & Baus, 2012;Münzer et al, 2006). Users of navigation systems showed good route memory but bad survey knowledge.…”
Section: Tools Affecting Acquisition Of Survey Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, mobile navigation systems take over guidance in real environments. This has detrimental effects on spatial learning: Münzer et al compared computer-assisted navigation to traditional map-based navigation and found differences in incidental knowledge acquisition (Münzer, Zimmer, & Baus, 2012;Münzer et al, 2006). Users of navigation systems showed good route memory but bad survey knowledge.…”
Section: Tools Affecting Acquisition Of Survey Knowledgementioning
confidence: 99%
“…They compared navigation with GPS devices to navigation with paper maps and to the direct experience, finding empirical evidence that users travelling with GPS devices acquire less survey knowledge. Münzer et al (2012) examined the effect of different visualization modes on incidental route and survey knowledge acquisition during an assisted tour through a real environment. When wayfinding instructions were presented in a "guidance mode" (turn-by-turn instructions from the egocentric perspective), then route memory was strengthened at the cost of survey knowledge.…”
Section: Tools Affecting Acquisition Of Survey Knowledgementioning
confidence: 99%
“…These cognitive maps are developed procedurally, building configurational understandings of a landscape over time (Kitchin 1996;Kitchin and Dodge 2007). Imparting configurational knowledge while providing adequate navigational visualizations and direction is a well-known challenge filled with tradeoffs in terms of mobile map and user interface design (Kitchin 1996;Kettunen et al 2012;Münzer et al 2012;Roth 2013).…”
Section: Spatial Cognitive Abilitiesmentioning
confidence: 99%
“…However, these types of instructions hinder spatial learning while there are types of visualizations in mobile devices that could support orientation learning incidentally (Muenzer et al 2012). Thus, we propose a new way of structuring wayfinding instructions which deviates from purely procedural instructions but a system that supports cognitive representation of the environment during wayfinding.…”
Section: Route Instructions Including Orientation Informationmentioning
confidence: 99%
“…These route instructions differ in their content and structure from human-given instructions: navigation systems give instructions that draw people's attention solely to the route and its turning points (turn-by-turn directions). Many researchers have evaluated the effectiveness of navigation assistance systems during wayfinding (Ishikawa et al 2008;Muenzer et al 2012;Brown and Laurier 2012) and showed that turn-by-turn (TbT) systems hardly support spatial learning. Studies in cognitive wayfinding research showed the importance of landmarks at decision points (Denis 1997;Daniel and Denis 1998;Richter and Klippel 2005).…”
Section: Introductionmentioning
confidence: 99%